Evaluasi Penerapan Belajar E-larning dalam pendalaman materi pada Universitas Wiralodra - Cyntiya Laxmi Haura; Tineke Fatma Putri; Taufik Hidayat (Jurnal Pengabdian Masyarakat Sultan Indonesia, 2024)
The face-to-face learning system is an effective method. However, there are several weaknesses in the face-to-face method, namely limited time for evaluation and discussion, because time is wasted during face-to-face meetings by delivering several courses. The aim of this research is to develop an E-learning prototype at Wiralodra University to complete the face-to-face learning system. Stages in building an E-Learning prototype apply the stages in the prototype model. Stages in building an E-Learning prototype apply the stages in the prototype model. This has three stages, namely receiving opinions from customers, building and improving prototypes, testing and evaluation. Apart from that, data collection techniques include observation, interviews, and building and improving prototypes.